Comparison of fatty acids profile on in vitro gastric digestion of raw milk of cow and goat with pancreatic lipase - Yasri, Yusmalaili (2016)
The main objective of this study was to determine the milk composition of raw milk of cow and goat. The specific objectives were to determine and compare the fatty acids profiles during in vitro gastric digestion of raw milk of cow and goat and at different time of digestion. Approximately 700 ml of milk bulk samples from cow (Ladang 16, UPM) and goat (Nilai Dairy Farm, Negeri Sembilan) were collected on the same day, without considering the breed, number of lactation and type of diet or other factors that might influence the milk composition. Both samples were analyzed for fat, protein, lactose and total solid content using milk. Balance of the milk samples then undergo in-vitro gastric digestion for 3 hours, to mimics the digestion of fats in human digestive system. During the 3 hours of in-vitro gastric digestion, samples were withdrawn at every 30 minutes intervals. Digested samples then undergoes the extraction and digestion processes prior to Fatty Acids Methyl Esters (FAME) by using chloroform-methanol. Fatty acids profiles in prepared samples were determined using Gas Chromatography machine (GC) 6890N Version N.04.08 (Agilent Technologies Inc., USA) fitted with HP-88 silica capillary column (100 m X 0.250 mm X 0.20 μm) (Agilent Technologies Inc., USA). The results of milk composition in cow and goat milk were significant different (P<0.05) for fat (4.41%; 3.09%), protein (3.08%; 2.66%), lactose (4.86%; 4.35%) and total solid (12.95%; 10.72%), respectively. The results on fatty acid profiles on in vitro gastric digestion was expected to reflect on milk composition especially on fat content when goat milk was observed high in beneficial fatty acids and highly digestible than cow milk.